Dual-Task Training Affect Cognitive and Physical Performances and Brain Oscillation Ratio of Patients With Alzheimer’s Disease: A Randomized Controlled Trial - Parvin, Elnaz; Mohammadian, Fatemeh; Amani-Shalamzari, Sadegh; Bayati, Mahdi; Tazesh, Behnaz (Frontiers in Aging Neuroscience, 2020)
This study aimed to investigate the effect of a 12-week period dual-task training on cognitive status, physical performance and brain oscillation of patients with Alzheimer's disease (AD). Twenty-six AD patients were randomly assigned to two groups, training group (TG) and control group (CG). TG executed progressive combined exercises with visual stimulation twice a week for 12 weeks. Training included muscle endurance, balance, flexibility and aerobic exercises with eyes closed and opened. Brain oscillation on EEG and a series of physical, cognitive and mental tests were taken prior and post intervention. There was a significant improvement after training protocol in cognitive function, particularly in short-term memory, attention, working memory and executive function (p<0.01). In addition, there were substantial improvements in depression status (GDS scale), aerobic fitness (6 min walking), flexibility (chair sit and reach) functional ability (chair stand, timed up and go test), strength (knee extensions, preacher biceps curl, handgrip) in TG compare to CG. These progresses was associated with significantly increase (p<0.05) in the frequency of brain oscillation and decreased in the theta/alpha ratio. In addition to physical performance, the regular combined training with visual stimulation improve brain health as indicated by improving cognitive function and reducing the theta/alpha ratio